2010
DOI: 10.1093/brain/awq322
|View full text |Cite
|
Sign up to set email alerts
|

The pedunculopontine nucleus area: critical evaluation of interspecies differences relevant for its use as a target for deep brain stimulation

Abstract: Recently, the pedunculopontine nucleus has been highlighted as a target for deep brain stimulation for the treatment of freezing of postural instability and gait disorders in Parkinson's disease and progressive supranuclear palsy. There is great controversy, however, as to the exact location of the optimal site for stimulation. In this review, we give an overview of anatomy and connectivity of the pedunculopontine nucleus area in rats, cats, non-human primates and humans. Additionally, we report on the behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 104 publications
6
103
0
Order By: Relevance
“…In addition, a meta-regression analysis of long-term studies suggested that GPI-DBS may provide more sustained benefit in preventing long-term decline in PIGD [10]. The mechanisms by which GPI-DBS improves postural control are uncertain, but it has been suggested that it may be due to descending effects on the pedunculopontine nucleus or other non-dopaminergic centres in the mesencephalic locomotor area [25]. Previous posturographic studies have shown that both GPI and STN stimulation can improve postural sway and balance reactions, including the capacity to respond to postural perturbations [9,14,15], but this was not investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a meta-regression analysis of long-term studies suggested that GPI-DBS may provide more sustained benefit in preventing long-term decline in PIGD [10]. The mechanisms by which GPI-DBS improves postural control are uncertain, but it has been suggested that it may be due to descending effects on the pedunculopontine nucleus or other non-dopaminergic centres in the mesencephalic locomotor area [25]. Previous posturographic studies have shown that both GPI and STN stimulation can improve postural sway and balance reactions, including the capacity to respond to postural perturbations [9,14,15], but this was not investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…During later phases of the disease, other signs and symptoms emerge, specifically gait and balance problems, and cognitive impairments. It is widely believed that balance problems are the result of degeneration in the portion of the PPN that belongs to the mesencephalic locomotor region and/or degeneration of cholinergic cell groups [e.g., 90,[133][134][135][136][137][138][139]. Cognitive impairments are likely caused by a combination of factors, including the extension of significant dopamine loss to nonmotor portions of the basal ganglia, and the spread of pathology to prefrontal cortical regions [132].…”
Section: Pathophysiology Of Parkinsonism and Dystoniamentioning
confidence: 99%
“…This constellation of findings suggests the possibility that the descending basal ganglia projections to the brainstem may play a greater role in the pathophysiology of akinesia/bradykinesia and movement than is commonly assumed. A particular role of the PPN in the axial control of gait and balance, and in abnormalities of these functions in patients with movement disorders, is suggested by the fact that portions of the PPN are part of the brainstem locomotor region [90,137,138], and the finding that PPN neurons in this region degenerate in PD [133][134][135][136].…”
Section: Pathophysiology Of Parkinsonism and Dystoniamentioning
confidence: 99%
“…The most common atlases used for DBS indicate that the PPN is located in the caudal mesencephalic tegmentum, extending from the caudal border of the red nucleus to the parabrachial nucleus [for extended review on PPN anatomy sees Alam et al, 2011]. The PPN is bordered medially by fibres of the superior cerebellar peduncle and its decussation and laterally by the medial lemniscus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further work should take into consideration the anatomical proximity between the caudal PPN and brainstem structures implicated in the control of micturition or their connections since electrical spread from the relatively large diameter of currently available DBS leads may affect nearby structures in an unpredictable manner in the compact human brainstem. 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 11 Neurosurgeons with an interest in the potential of the PPN as a DBS target in PD (Jenkinson et al, 2005;Stefani et al, 2007;Alam et al, 2011) should be aware of the location and important functions of these nuclei.…”
Section: Discussionmentioning
confidence: 99%